Disability, gender, and the British labour market - Melanie Jones (Oxford Economic Papers, 2006)
Using UK LFS data, we examine the impact of disability on labour market outcomes by gender since the Disability Discrimination Act. Substantial differences in employment incidence and earnings continue to exist, especially for those with mental health problems. Distinguishing between work-limiting and non-work-limiting disability, the unobserved productivity effect of disability can be separated from discrimination. Limited evidence of wage discrimination against the disabled exists, but the ‘penalty’ for work-limiting disability, while falling for men, has increased for women. The improvement for disabled males is largely ‘unexplained’, possibly reflecting the impact of the legislation; this is not the case for females.